Using DEA for regional merging zones based on geographic models of the European economy - Staníčková, Michaela; Melecký, Lukáš (Univerzita Pardubice, 2016)
For centuries, the “Blue Banana”, metropolitan axis running from London to Milan, has been Europe’s breeding place for innovation and growth. Recently, the “Sunbelt” from Milan to Valencia and the “Yellow Banana” from Paris to Warsaw have been identified as future European growth poles beside or even beyond the Blue Banana. Europe’s competitiveness depends on a multiplicity of actions that can optimise the potentials within its territory, especially regions. Nowadays, regions are increasingly becoming the drivers of the economy. All regions possess development opportunities – however, use these options enough and hence the competitiveness of European regions must be efficient enough. It is well-known that there are significant differences among the European Union regions which weaken its competitiveness. What are differences in territorial efficiencies with respect to the structure of Europe’s economic-geographical system? The paper is focused on using SBMT VRS DEA model for dividing NUTS 2 regions from geographic models of the European economy into efficient and inefficient ones. The main aim of the paper is to find the efficient frontier and identify optimal benchmark for inefficient regions as a strategy for enhancing their economic structure.
Keywords: competitiveness; efficiency; geographic model; NUTS 2 region; SBMT VRS DEA model; super-efficiency; C61; C67; O18; R11; R13; R15; R58